(untitled) (American International Journal of Agricultural Studies, 2024)
Humic acids are organic compounds that enhance agronomic parameters, plant growth, and soil characteristics. Humic acid-based products have recently been utilized in crop production to maintain the sustainability of agricultural output. Humic acid can enhance a variety of physical, chemical, and biological properties of soil, including texture, structure, water-holding capacity, cation exchange capacity, pH, soil carbon, enzymes, nitrogen cycling, and nutrient availability. This study emphasizes the significance of humic acid for crop growth, plant hormone production, nutrient uptake and assimilation, Yield, and protein synthesis. The study deals with the Effect of humic acid on growth, fruit weight, fruit volume, quality of fruit, and Yield per hectare of ridge gourd. The research was studied at the In-check Farm, BCKV, Mohanpur, Nadia, W.B., India, in the pre-kharif season of 2023, following RBD with three replications, seven treatments, and control. Among the treatments, T6 had the highest fruit yield (127.908 q ha-1), followed by T5 in second place (109.842 q ha-1) and T1 in last place (70.480 q ha-1), with a significant difference between them. The average fruit yield and parameters associated with Yield were significantly higher for ridge gourds when 112 kg ha-1 of humic acid was applied in conjunction with the recommended dosage of fertilizers (T6). In all cases except days to flower initiation, T6 was highest among the other treatments. Hence, the humic acid (112 kg ha-1) along with FYM @ 20 kg ha-1, neem cake @ 600 kg ha-1, N @ 50 kg ha-1, P2O5 @ 25 kg ha-1, and K2O @ 25 kg ha-1 fertilizers were recommended for getting the maximum Yield, and quality of ridge guard. JEL Classification Codes: Q22, Q120.